1998
DOI: 10.1038/sj.bjp.0701924
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antioxidant activities of aminoguanidine, methylguanidine and guanidine by luminol‐enhanced chemiluminescence

Abstract: 1 The objective of this study was to investigate the ability of aminoguanidine, methylguanidine and guanidine to inhibit free radicals or metabolites generated by either stimulated human leucocytes or cellfree systems using luminol-enhanced chemiluminescence (CL). 2 Aminoguanidine (0.1 mM ± 10 mM), methylguanidine (10 mM ± 10 mM) and guanidine (10 mM ± 10 mM) produced concentration-dependent inhibition (96+0.1%, n=7, 59+1.3%, n=6, and 62+3%, n=6, P50.05 at 10 mM, respectively) in FMLP-stimulated leucocytes CL.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 32 publications
1
68
0
1
Order By: Relevance
“…27 Previous studies pointed out the beneficial antioxidant effects of AG and scavenger effects of ONOO -which is a reactive oxidant produced from NO and O 2-in various forms of tissue injury. 35 Yildiz et al 36 also found that AG had direct scavenging activities against HO. Recently, Giardino et al 37 reported that AG acts as an antioxidant in vivo, preventing ROS formation and lipid peroxidation in cells and tissues, thus preventing oxidant-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Previous studies pointed out the beneficial antioxidant effects of AG and scavenger effects of ONOO -which is a reactive oxidant produced from NO and O 2-in various forms of tissue injury. 35 Yildiz et al 36 also found that AG had direct scavenging activities against HO. Recently, Giardino et al 37 reported that AG acts as an antioxidant in vivo, preventing ROS formation and lipid peroxidation in cells and tissues, thus preventing oxidant-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…40 The beneficial effects of AG in various experimental models of inflammation have also been reported. 41 Recently, Mansour et al 36 reported that AG protects against nephrotoxicity induced by cisplatin (CDDP) in rats. The beneficial antioxidant effects of AG and the scavenger effects of ONOO -, which is a reactive oxidant produced from NO and superoxide (O -), have been observed in various forms of tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of iNOS by AG may ameliorate the cognitive defi cit induced by diabetes (38). Other neuroprotective mechanisms of AG may be related to its free radical scavenging properties (35,39). Also, a number of cellular metabolic pathways about AG neuroprotective functions relate to methylglyoxal (MG) inhibition (40).…”
Section: Discussionmentioning
confidence: 99%
“…GPx activity was slightly decreased after AG treatment in a model of liver injury in rat [31] . Chronic treatment with AG might cause a disruption of the cellular redox balance due to its capacity to scavenge oxidant reactive species [32] and to inhibit NO synthesis. This could explain the reduced expression of antioxidant enzymes as a compensatory mechanism.…”
Section: Discussionmentioning
confidence: 99%